2022
DOI: 10.3390/pathogens12010030
|View full text |Cite
|
Sign up to set email alerts
|

Xiaochaihu Decoction Treatment of Chicken Colibacillosis by Improving Pulmonary Inflammation and Systemic Inflammation

Abstract: Chicken colibacillosis—the most common disease of poultry, is caused mainly by avian pathogenic Escherichia coli (APEC). It has a major impact on the poultry industry worldwide. The present study was conducted to investigate the therapeutic effects of Xiaochaihu Decoction (XCHD) supplementation on clinical manifestation, organ index, bacterial load in organ and inflammatory mediators in a chicken model challenged with APEC. The results showed that all doses of XCHD significantly elevated the survival rate of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…During APEC infection, immune cells release cytokines in response to bacterial invasion, causing other immune cells to be activated and recruited to the infection site. The sequential development of inflammatory reaction over the course of colisepticaemia in this study coincided with a recently published work, which showed that APEC infection led to massive secretion of proinflammatory cytokines like IL-1β, IL-6 and TNF-α expression in the lung and serum 46 . Likewise, we also showed previously that IL-1β and IL-6 can be upregulated in lung and spleen at 3 dpi 10 .…”
Section: Discussionsupporting
confidence: 90%
“…During APEC infection, immune cells release cytokines in response to bacterial invasion, causing other immune cells to be activated and recruited to the infection site. The sequential development of inflammatory reaction over the course of colisepticaemia in this study coincided with a recently published work, which showed that APEC infection led to massive secretion of proinflammatory cytokines like IL-1β, IL-6 and TNF-α expression in the lung and serum 46 . Likewise, we also showed previously that IL-1β and IL-6 can be upregulated in lung and spleen at 3 dpi 10 .…”
Section: Discussionsupporting
confidence: 90%
“…Bacterial load testing was based on previous reports ( Song, et al, 2022 ), in brief, bacterial DNA was extracted from 10 8 CFU/mL of APEC bacterial solution by tenfold dilution to 10 2 CFU/mL. 16S rRNA primer sequences (5′-3′): F-CACAATGGGCGAAAGCCTGA; R-GGCTGCTGGCACGTAGTTAG.…”
Section: Methodsmentioning
confidence: 99%